(untitled) (Research, Society and Development, 2020)
This study presents research on the topic of Environmental Ethics and the View of the Academics of the Environmental Management course at IFMT - Campus Bela Vista. It aimed to work on the concept of environmental ethics relating it to environmental education and legislation, and also to analyze the views of future environmental managers regarding these concepts, which are constantly addressed in their training. Having as main referential base the book Ética Ambiental of the author Nalini (2010), together with research of articles in virtual database, having the term environmental ethics as a descriptor used in the searches. The applied methodology was a bibliographic review of the themes: concept of ethics, education and environmental legislation and a field research with environmental management students. As a result of the research, it was possible to notice that the students’ conception of the concepts still permeated common sense and did not relate one sphere with the other. Namely ethics, educational and financial.